Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

f(x)= -5x-1 and g(x)= 2x^2
solve (f+g)(x)


Sagot :

[tex]f(x)=-5x-1;\ D_f:x\in\mathbb{R}\\\\g(x)=2x^2;\ D_g:x\in\mathbb{R}\\\\D_f=D_g\ then\ (f+g)(x)=f(x)+g(x)\\\\(f+g)(x)=-5x-1+2x^2=2x^2-5x-1[/tex]
View image Аноним
Xhade
[tex] \{f + g \}(x) = (-5x - 1 )\ +\ 2 x^{2} \\\\= 2 x^{2} -5x - 1\ \ Answer[/tex]